A study on an altitudinal gradient investigating the potential effects of climate change on fynbos and the Fynbos-Succulent Karoo boundary - Agenbag, Lize (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 2006.